Pengaruh Layanan Perpustakaan Terhadap Kepuasan Pemustaka Di Perpustakaan SMP Negeri 3 Rantau Bayur Kabupaten Banyuasin - Yoanda, Sely; Tridana, Anggi; Gunaidi, Aang (Jurnal Tadwin, 2023)
User satisfaction is a benchmark in efforts to improve library services. The aims of this study were: (1) to find out what services are available at the Library of SMP Negeri 3 Rantau Bayur, Banyuasin Regency; (2) to find out the effect of library services on user satisfaction at the Library of SMP Negeri 3 Rantau Bayur, Banyuasin Regency. The research method used is decriptive qualitative with data collection techniques through observation, interviews, and documentation. The informants in this study were library users at the SMP Negeri 3 Rantau Bayur, Banyuasin Regency, namely students, and teachers or education staff. The results in this study obtained data, namely: (1) the services available at the library include: library service hours, circulation services, reference services, reading room service, user education program, compulsory reading programs in the library, information literacy programs, library promotions, holding doorpize for users who frequently do visit, student showcase; (2) the services provided have an influence on user satisfaction. The conclusion in this study is that the Library of SMP Negeri 3 Rantau Bayur, Banyuasin Regency must optimize the services provided so that users are more satisfied, so that the interest of visiting users to the library also increases.